2012
DOI: 10.1002/hbm.22090
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the perception of contrastive prosodic focus in French: A functional magnetic resonance imaging study

Abstract: This functional magnetic resonance imaging (fMRI) study aimed at examining the cerebral regions involved in the auditory perception of prosodic focus using a natural focus detection task. Two conditions testing the processing of simple utterances in French were explored, narrow-focused versus broad-focused. Participants performed a correction detection task. The utterances in both conditions had exactly the same segmental, lexical, and syntactic contents, and only differed in their prosodic realization. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 89 publications
(137 reference statements)
0
12
0
Order By: Relevance
“…Prevailing models of prosody perception do not typically include the parietal lobe (Brück et al, 2011;Schirmer & Kotz, 2006;Wildgruber et al, 2006;Wildgruber, Ethofer, Grandjean, & Kreifelts, 2009;Witteman, Van Heuven, & Schiller, 2012); nevertheless, right inferior parietal activations (BA 40/7) have been occasionally reported in prosody studies (Belyk & Brown, 2014;Merrill et al, 2012) and were proposed to reflect rehearsal-based working memory processes for prosodic pitch contours (Kreitewolf et al, 2014;Perrone-Bertolotti et al, 2013). The present study cannot discriminate between neural mass effects and changes in white matter conductivity.…”
Section: Focality Of Edema-induced Disruptionsmentioning
confidence: 57%
“…Prevailing models of prosody perception do not typically include the parietal lobe (Brück et al, 2011;Schirmer & Kotz, 2006;Wildgruber et al, 2006;Wildgruber, Ethofer, Grandjean, & Kreifelts, 2009;Witteman, Van Heuven, & Schiller, 2012); nevertheless, right inferior parietal activations (BA 40/7) have been occasionally reported in prosody studies (Belyk & Brown, 2014;Merrill et al, 2012) and were proposed to reflect rehearsal-based working memory processes for prosodic pitch contours (Kreitewolf et al, 2014;Perrone-Bertolotti et al, 2013). The present study cannot discriminate between neural mass effects and changes in white matter conductivity.…”
Section: Focality Of Edema-induced Disruptionsmentioning
confidence: 57%
“…Previous fMRI studies, however, have not studied this use of prosody. Rather, fMRI research has focused on types of linguistic prosody which are not as crucial for the syntactic structure of a sentence, such as marking a question or statement (Kreitewolf et al, 2014;Sammler et al, 2015) or placing stress (Kristensen et al, 2013;Perrone-Bertolotti et al, 2013). Moreover, studies often used a lowlevel or non-linguistic baseline condition rather than a comparable linguistic control task (Meyer et al, 2002;Plante et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined based on previous fMRI studies on sentence processing (e.g. Goucha & Friederici, 2015;Kristensen, Wang, Petersson, & Hagoort, 2013;Perrone-Bertolotti, Dohen, Loevenbruck, Sato, Pichat & Baciu 2013). The exclusion criteria were established prior to data analysis.…”
Section: Participantsmentioning
confidence: 99%
“…In a recent fMRI study, Perrone-Bertolotti et al (2013) found a comparable lateralized network to be activated during the auditory perception of prosodic focus when participants had to decide whether or not the sentences they heard contained contrastive focus (on the subject or the object) or not. The authors interpreted their finding of increased activation in temporal, parietal, and frontal regions during focused as compared to neutral condition in the context of the dual stream framework.…”
Section: Neural Activation Pattern Underlying Rhyme and Meter Detectionmentioning
confidence: 97%
“…The authors interpreted their finding of increased activation in temporal, parietal, and frontal regions during focused as compared to neutral condition in the context of the dual stream framework. While they attributed the right dominant STG activation to longer timescale computations and involvement of the ventral stream, the activation in the parietal and frontal regions was explained by an interplay between the two hemispheres in a auditory-motor hub and thus involvement of the dorsal stream (Perrone-Bertolotti et al, 2013).…”
Section: Neural Activation Pattern Underlying Rhyme and Meter Detectionmentioning
confidence: 98%